Free Radical Scavenging and Total Antioxidant Capacity of Combined Methanol Leaf Extract of Solanum americanum and Polyalthia longifolia - Asadu, Chidimma Lilian; Uroko, Ikechukwu Robert; ugwu, Obiora Celestine (Biology, Medicine, & Natural Product Chemistry, 2025)
The present investigation highlights the phytochemical composition and free radical scavenging activity of methanol leaf extract of Solanum americanum and Polyalthia longifolia. The fresh leaves of S. americanum and P. longifolia were air-dried, milled into powder and macerated into absolute methanol. The extract was subjected to phytochemical screening and in-vitro antioxidant activity which was compared with that of standard Ascorbic acid. The qualitative quantitative phytochemical screening results constitutes flavonoids (43.05 mg/g), phenols (71.93 mg/g), alkaloids (34.11 mg/g), terpenoids (18.09mg/g), saponin (5.47 mg/g) and tannins (26.17 mg/g) all of which are known for their therapeutic properties. The antioxidant activity was evaluated using the DPPH (2, 2-diphenyl-1-picrylhydrazyl), total antioxidant capacity (TAC) and FRAP (Ferric Reducing Antioxidant Power) assays, which showed significant percentage inhibition in dose dependent manner. The combined extract exhibited significant DPPH radical scavenging activity with an Ec50 value of 0.993µg/ml, highlighting their potent radical scavenging ability. Furthermore, the FRAP assay revealed a high reducing power in the highest concentration (800ug/ml) having 79.1 µMFe2+/g, suggesting effective electron donation capabilities. The total antioxidant capacity results obtained showed that the TAC for the extract was in the range of 0. 650 to 2.123 AAE (ascorbic acid equivalent) for the different concentrations used.